Identifying the Barriers and Drivers of Transit Oriented Development (TOD) Implementation in Southeast Asia: A Comparative Analysis of TOD Implementation and Resources and Tools by World Bank (WB) and Identified Developing Southeast Asian Countries TOD Policies - Giron, Gene Lambert R.; Punnoi , Nattapong (MAJ - Malaysia Architectural Journal, 2025)
Transit-oriented developments (TOD) have been implemented worldwide to increase population density, pedestrian-friendliness, public transportation usage, and economic growth by creating well-planned and integrated urban areas. Thus, development agencies such as the Asian Development Bank (ADB), Japan International Cooperation Agency (JICA), and World Bank, to name a few, are helping their member and borrowing countries to promote TODs by investing in mass-rapid transit and addressing financial gaps to make Southeast Asian cities liveable by 2030. Despite traffic congestion, Singapore and Malaysia successfully pioneered TOD in the region. At the same time, Thailand, Indonesia, the Philippines, and Vietnam have recently implemented national and local policies to replicate this success in their major urban centers. As borrowing members of the World Bank, these countries must adhere to the TOD Implementation Resources and Tools, a publication by the said agency that helps implement TOD. Although these nations tried to achieve similar success, they needed help implementing the reference. Hence, a Comparative Content Analysis between the TOD policies of the select Southeast Asian countries and TOD Implementation Resources and Tools was conducted where four main criteria were examined: TOD Planning, Station Area Development, Stakeholder and Community Collaboration, and Value Capture was found that Southeast Asian countries' policies must address and improve various policy barriers on transit accessibility, pedestrian-friendliness, liveable public facilities, surrounding developments, affordable housing and accessible living, mixed-uses and suitable urban forms, stakeholder and community collaboration, and value capture mechanisms, and the TOD implementation resources and tools to include in their policies on the empowerment of local culture and identity. This will help promote genius loci and esprit de corps to existing and future TODs.